It’s Not “Personal”: Health Information Disclosure and the Physical- Mental Distinction - Covo, Yaron; Klug, Trevan; Olgun, Melisa; Ahmed Ramy, Mohamed; Darji, Rayyan; Gupta, Mihir (The Columbia Journal of Law & the Arts, 2026)
For almost eight decades, U.S. sports leagues have disclosed information about athletes’ health with the stated goal of protecting the integrity of sports from bettingrelated manipulations. The leagues’ treatment of such information, however, has been inconsistent: When professional athletes miss games due to physical injuries, leagues usually disclose such injuries in great specificity. By contrast, when players miss a game due to mental health issues, their absence is simply attributed to “personal reasons.” This Article documents this disparity and situates it within existing regulatory frameworks in the areas of privacy law, disability law, and sports betting regulation. The Article’s main argument is that this practice cannot be justified on either factual or normative grounds. On the factual side, we review medical research showing that a stark dichotomy between “physical” and “mental” health is incompatible with the modern recognition that the body and the mind are interrelated systems. On the normative side, we argue that treating mental health issues as “personal reasons” may exacerbate the preexisting stigma surrounding mental health, may imply that mental health issues are not “real,” and may obscure the sports leagues’ responsibility for such issues. To address these problems, this Article proposes several alternative methods of disclosing health status, taking into account the importance of preserving athletes’ autonomy in regard to their mental health reporting. We conclude by discussing how the implications of this analysis may extend beyond the sports arena.